Development of AI-Enhanced Learning-Based Constructivist Training E-Module to Improve The Pedagogic Competence of Junior High School Teachers Through the Professional Learning Community - Berlian Novalita Sigalingging; Bambang Ismanto; Stefanus C. Relmasira (CV. Creative Tugu Pena, 2026)
This research is motivated by the low pedagogical competence of teachers in implementing constructivist learning and the minimal use of AI-Enhanced Learning technology at SMP Negeri 4 Sentani. Existing conventional training is considered ineffective in providing practical guidance on technology integration in learning. This study aims to develop a training E-Module that has been tested for validity, practicality, and effectiveness in improving teacher pedagogical competence through the Professional Learning Community (PLC) forum. Using the modified Borg and Gall Research and Development (R&D) model method. Field trial subjects involved 30 teachers. Data collection techniques used interviews, observations, questionnaires, and tests, which were analyzed using quantitative descriptive and inferential statistics (t-test and N-Gain). The results showed that the E-Module met the criteria of very valid (material experts: 3,69; media experts: 3,95) and very practical (91,05%). The effectiveness test showed a significant increase in competence (Sig. 0.000) with an N-Gain score of 0.76 (High category). The AI-Enhanced Learning-Based Constructivism Training E-Module has been proven to be feasible and effective in improving teachers' pedagogical competence and digital literacy, as well as being able to build a collaborative culture in PLC.